Salivary metabolome indicates a shift in tyrosine metabolism in patients with burning mouth syndrome: a prospective case–control study. Issue 3 (29th March 2023) - Moreau, Charlotte; El Habnouni, Chakib; Lecron, Jean-Claude; Morel, Franck; Delwail, Adriana; Le Gall-Ianotto, Christelle; Le Garrec, Raphaele; Misery, Laurent; Piver, Eric; Vaillant, Loïc; Lefevre, Antoine; Emond, Patrick; et al.
Abstract : Supplemental Digital Content is Available in the Text. The observed shift in the tyrosine pathway in saliva of burning mouth syndrome patients may indicate an adaptative response to chronic pain or an impaired dopaminergic transmission. Abstract: The pathophysiology of primary burning mouth syndrome (BMS) remains controversial. Targeted analyses or "omics" approach of saliva provide diagnostic or pathophysiological biomarkers. This pilot study's primary objective was to explore the pathophysiology of BMS through a comparative analysis of the salivary metabolome among 26 BMS female cases and 25 age- and sex-matched control subjects. Secondary objectives included comparative analyses of inflammatory cytokines, neuroinflammatory markers, and steroid hormones among cases and control subjects, and among BMS patients according to their clinical characteristics. Salivary metabolome, neuroinflammatory markers, cytokines, and steroids were, respectively, analysed by liquid chromatography coupled with mass spectrometry, ELISA and protease activity assay, and multiparametric Luminex method. Among the 166 detected metabolites, univariate analysis did not find any discriminant metabolite between groups. Supervised multivariate analysis divided patients into 2 groups with an accuracy of 60% but did not allow significant discrimination (permutation test, P = 0.35). Among the metabolites contributing to the model, 3 belonging to the tyrosine pathway (l -dopa, l -tyrosine, and tyramine) were involved in the discrimination between cases and control subjects, and among BMS patients according to their levels of pain. Among the detectable molecules, levels of cytokines, steroid hormones, and neuroinflammatory markers did not differ between cases and control subjects and were not associated with characteristics of BMS patients. These results do not support the involvement of steroid hormones, inflammatory cytokines, or inflammatory neurogenic mediators in the pathophysiology of pain in BMS, whereas the observed shift in tyrosine metabolism may indicate an adaptative response to chronic pain or an impaired dopaminergic transmission.